Edukasi mengenai Penyakit Anemia pada Kalangan Remaja dengan Penyuluhan Kesehatan di SMA Negeri 2 Banjar - Wulan Permata s; VINA APRELIA; Yuda Nugraha; Dhani (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2021)
Introduction: Anemia is a condition where the level of hemoglobin (Hb) in a person's blood is lower than the normal value. Anemia can be grouped according to age and gender. The cause of anemia in countries with anemia prevalence above 20% is iron deficiency anemia or a combination of iron deficiency. Anemia occurs due to lack of iron so that the formation of red blood cells and other functions in the body is disrupted. In Indonesia 2 The prevalence of anemia in the age group 5-14 years is 26.4% and in the age group 15-24 years is 18.4%. The cause of nutritional anemia, generally is due to the intake of foods that contain low iron. Objective: The purpose of this health education is to increase knowledge about anemia and to assist in early prevention of anemia cases among adolescents. Method: The method used in this activity is an observational method and a question-and-answer discussion method where this activity begins with looking for targets or counseling subjects. Result: Based on the results of research conducted on 20 respondents on November 10, 2021 at SMA Negeri 2 Banjar, the data obtained based on BMI characteristics, the majority 95% had normal nutritional status, had normal menstrual patterns, never had a history of disease, but the consumption pattern of Fe tablets in all respondents (100%) are irregular. Conclussion: In accordance with the evaluation results, this educational activity regarding anemia in adolescents has been successful with indicators of Timeliness and Duration, Participation, Knowledge and Problem Solving.